Artificial Intelligence in 21st Century Arabic Language Education: Students’ Perceptions and Its Impact on Developing Critical Thinking Skill - Anggi Nurul Baity; Putri Kholida Faiqoh; Aulia Golda Mutarto; Maziyyatul Muslimah (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2026)
The rapid expansion of Artificial Intelligence (AI) in the digital era has begun to reshape how students learn foreign languages, including Arabic. Beyond offering convenience and efficiency, AI tools increasingly influence how students think, process information, and construct knowledge. This study explores students’ perceptions of AI use in 21st-century Arabic language learning and examines how it affects the development of critical thinking skills, particularly the higher-order cognitive processes of analysis, evaluation, and creation as conceptualized in Bloom’s Taxonomy. Using a qualitative thematic approach, data were collected through questionnaires from 98 students enrolled in the Arabic Language Education Program at the Faculty of Tarbiyah, UIN Syekh Wasil Kediri. The findings show that AI supports analytical thinking (C4) by assisting students in breaking down complex Arabic texts, identifying linguistic patterns, and comparing alternative structures with greater clarity. In terms of evaluative thinking (C5), AI encourages students to question interpretations and check the accuracy of information; however, when used uncritically, it may weaken independent judgment as some students tend to accept AI-generated responses without deeper reflection. Regarding creative thinking (C6), AI helps students generate ideas, organize arguments, and experiment with language production, yet excessive dependence can limit originality and reduce opportunities for authentic knowledge construction. Importantly, many students demonstrate awareness of these challenges and adopt adaptive strategies, such as selectively using AI, verifying outputs with credible sources, and reformulating information in their own words. These findings suggest that AI does not inherently diminish critical thinking; rather, its impact depends on how consciously and pedagogically it is integrated into the learning process. When guided appropriately, AI can serve as a supportive cognitive partner in fostering higher-order thinking in Arabic language education.